Edukasi dan Skrining Hipertensi pada Pekerja Pengrajin Sandal di Industri Sektor Informal X Kota Tasikmalaya 2025 - Rani Aprilia; Alpina Daayanti; Nenih Nurhasanah; Alifa Kanasya Sukasah; Euis Tiara Yuliandani; Nawal Nur Ramadhani; Fitria Pancara Gunawati (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This community service activity aimed to increase the knowledge and awareness of informal sector sandal craftsmen regarding hypertension through education and blood pressure screening. The target group consisted of 17 workers at Sandal Factory X in Tasikmalaya City. The methods used included health education using interactive poster media and blood pressure screening with a digital sphygmomanometer. The results showed that most workers (94.1%) had elevated blood pressure: 41.2% pre-hypertension, 41.2% stage 1 hypertension, and 11.8% stage 2 hypertension. Only 5.9% had normal blood pressure. This activity effectively raised participants’ awareness of the importance of early detection of hypertension. The workers responded positively and showed enthusiasm in participating. These findings highlight the importance of promotive and preventive interventions for informal sector workers who are often underserved in healthcare access.